Ventilasi Mandiri terhadap Stres pada Penyintas COVID-19 dengan Diabetes Mellitus - Vania Aresti Yendrial; Arina Widya Murni; Esi Afriyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of self-ventilation on stress and blood sugar levels in survivors of Covid-19 with diabetes mellitus. This research method is a quasi-experimental design with a nonequivalent control group design. The results showed that the average stress of respondents in the intervention group before self-ventilation was 36.44, with a standard deviation of 1,917. After self-ventilation, the moderate pressure was 29.56 with a standard deviation of 3,124 (95% CI 5,376 - 8,384). In conclusion, there was an effect on the average stress of COVID-19 survivors with diabetes mellitus in the intervention group. In contrast, in the control group, there was no effect of self-ventilation on the moderate pressure of COVID-19 survivors with diabetes mellitus. Keywords: Diabetes mellitus, COVID-19 survivors, stress, self-ventilation